Magellanic penguin (Spheniscus magellanicus) embryos tolerate high temperature variations and low temperatures during incubation - Barrionuevo, Melina (2012)
Maintaining appropriate developmental temperatures during avian incubation is costly to the parents, so embryos may experience pronounced variations in temperature that can lead to embryo mortality and extended incubation periods, or that could affect the offspring phenotype in several bird species. The egg temperatures (N = 28 eggs) of free-living Magellanic Penguins (Spheniscus magellanicus) were recorded in a breeding colony in Puerto Deseado, Santa Cruz, Argentina. Three nests had atypical incubation patterns. Two nests experienced high temperature drops (average = 11.7 °C, minimum = 6.5°C, duration = 9 h) and another nest had a broad daily temperature range (max-min), i.e. 13.9 ±0.9 °C for the first egg and 14.1 ±0.8 °C for the second egg (range = 8-22°C during egg laying and 1837°C during advanced incubation). Thermal anomalies during incubation did not affect the embryonic viability, hatchling mass or fledging success. The survival of embryos despite these atypical incubation patterns may be an adaptive mechanism during the harsh weather conditions normally experienced by eggs throughout incubation.